Characterization of Foci and Breakthrough Sites During Persistent and Long‐Standing Persistent Atrial Fibrillation in Patients: Studies Using High‐Density (510–512 Electrodes) Biatrial Epicardial Mapping. Issue 3 (March 2017) - Lee, Seungyup; Sahadevan, Jayakumar; Khrestian, Celeen M.; Markowitz, Alan; Waldo, Albert L.
Abstract : Background: We previously demonstrated that persistent and long‐standing persistent atrial fibrillation is maintained by activation emanating from foci and breakthrough sites of different cycle lengths (CLs). The purpose of this study was to characterize the behavior of focal and nonrandom breakthrough activation identified during high‐density mapping of atrial fibrillation in these patients. Methods and Results: During open heart surgery, we recorded activation from both atria simultaneously using 510 to 512 epicardial electrodes along with ECG lead II in 12 patients with persistent and long‐standing persistent atrial fibrillation. For each patient, analysis of 32 consecutive seconds of activation from identified focal (sustained and/or intermittent) and nonrandom breakthrough sites was performed. Multiple foci (sustained and/or intermittent) of different CLs were present in both atria in 11 of 12 patients; 8 foci were sustained, and 22 were intermittent. Temporal CL behavior of sustained foci varied over time (≤20 ms of the mean CL). For intermittent foci, no activation periods were due to a spontaneous pause (18 of 22) or activation of the focus by another wave front (11 of 22). All patients had breakthrough activation. Seven patients had 12 nonrandom breakthrough sites. Periods of no breakthrough activation were caused by a spontaneous pause (6 of 12 patients) or activation from another wave front (4 of 12) or were uncertain (5 of 12). Focal and nonrandom breakthrough activation sometimes produced repetitive "wannabe" (incomplete) reentry in 6 of 12 patients. Conclusions: During persistent and long‐standing persistent atrial fibrillation, sustained foci manifested variable CLs. Spontaneous pauses or activation from other wave fronts explained the intermittency of foci and nonrandom breakthrough. Focal and nonrandom breakthrough activation occasionally produced wannabe reentry.